Novel Putative Positive Modulators of α4β2 nAChRs Potentiate Nicotine Reward-Related Behavior - Skylar Y. Cooper; Austin T. Akers; Velvet Blair Journigan; Brandon J. Henderson (Molecules, 2021)
The popular tobacco and e-cigarette chemical flavorant (−)-menthol acts as a nonselective, noncompetitive antagonist of nicotinic acetylcholine receptors (nAChRs), and contributes to multiple physiological effects that exacerbates nicotine addiction-related behavior. Menthol is classically known as a TRPM8 agonist; therefore, some have postulated that TRPM8 antagonists may be potential candidates for novel nicotine cessation pharmacotherapies. Here, we examine a novel class of TRPM8 antagonists for their ability to alter nicotine reward-related behavior in a mouse model of conditioned place preference. We found that these novel ligands enhanced nicotine reward-related behavior in a mouse model of conditioned place preference. To gain an understanding of the potential mechanism, we examined these ligands on mouse α4β2 nAChRs transiently transfected into neuroblastoma-2a cells. Using calcium flux assays, we determined that these ligands act as positive modulators (PMs) on α4β2 nAChRs. Due to α4β2 nAChRs’ important role in nicotine dependence, as well as various neurological disorders including Parkinson’s disease, the identification of these ligands as α4β2 nAChR PMs is an important finding, and they may serve as novel molecular tools for future nAChR-related investigations.